Evaluation of Sea Ice Concentration Data Using Dual-Polarized Ratio Algorithm in Comparison With Other Satellite Passive Microwave Sea Ice Concentration Data Sets and Ship-Based Visual Observations - Zong, Fangyi; Zhang, Shugang; Chen, Ping; Yang, Lipeng; Shao, Qiuli; Zhao, Jinping; Wei, Lai (Frontiers in Environmental Science, 2022)
The dual-polarized ratio (DPR) algorithm is a new algorithm that enables calculation of Arctic sea ice concentration (SIC) from the 36.5-GHz channel of the sensor Advanced Microwave Scanning Radiometer for EOS/Advanced Microwave Scanning Radiometer 2 (AMSR-E/AMSR2). In this paper, we demonstrate results that the SIC data using DPR algorithm (DPR-AMSR) are evaluated and compared with other eight Arctic SIC data products with respect to differences in SIC, sea ice area (SIA), and sea ice extent (SIE). On a pan-Arctic scale, there were widespread positive and negative differences in SIC that were within ±0.05 between DPR-AMSR and the bootstrap algorithm from AMSR-E/AMSR2 (BT-AMSR), the bootstrap algorithm from SSM/I or SSMIS (BT-SSMI), the ARTIST Sea Ice algorithm from AMSR-E/AMSR2 (ASI-AMSR), and the enhanced NASA Team algorithm from AMSR-E/AMSR2 (NT2-AMSR). However, European Space Agency Climate Change Initiative algorithm from AMSR-E/AMSR2 (SICCI-AMSR), the European Organisation for the Exploitation of Meteorological Satellites Ocean and Sea Ice Satellite Application Facility from SSM/I or SSMIS (OSI-SSMI), the ARTIST Sea Ice algorithm from SSM/I or SSMIS (ASI-SSMI), and the NASA Team algorithm from SSM/I or SSMIS (NT1-SSMI) are all lower than DPR-AMSR at sea ice edge. ASI-SSMI was within −0.1 to −0.05; SICCI-AMSR, OSI-SSMI and NT1-SSMI were all less than −0.1. The difference of SIA was consistently within ±0.5 million km2 between DPR-AMSR and BT-AMSR, BT-SSMI, ASI-AMSR, and NT2-AMSR in all years. The difference of SIA between DPR-AMSR and SICCI-AMSR, OSI-SSMI, ASI-SSMI, and NT1-SSMI was less than −0.5 million km2. The smallest difference was with BT-SSMI (less than 0.1 million km2), whereas the largest difference was with NT1-SSMI (up to 1.5 million km2). In comparisons of SIE, BT-AMSR, NT1-SSMI, and NT2-AMSR estimates were consistent with that of DPR-AMSR and were within ±0.5 million km2. However, differences exceeded 0.5 million km2 between DPR-AMSR and the other data sets. When ship-based visual observation (OBS) values ranged from 0.85 to 1, the difference between DPR-AMSR and OBS was less than 0.01. There were relatively large differences between DPR-AMSR and OBS when OBS values were less than 0.85 or were recorded during the summer, although those differences were also within 0.1.